1982
DOI: 10.1128/iai.35.3.1011-1017.1982
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxic cells induced after Chlamydia psittaci infection in mice

Abstract: The ability of spleen cells from Chlamydia psittaci-infected mice to lyse C. psittaci-infected and uninfected target cell monolayers was studied. The cytotoxicity assay used was a terminal label method in which the number of adherent target cells surviving the interaction with effector cells was determined by measuring the uptake of [3H]uridine by such cells. It was observed that in the first few days postinfection (3 to 5), spleens contained cells that lysed infected and uninfected targets with equal efficien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
13
0

Year Published

1988
1988
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(15 citation statements)
references
References 28 publications
2
13
0
Order By: Relevance
“…Because of the obligate intracellular lifestyle of C. trachomatis, it has been thought that CTL may also be involved in immunity to this pathogen. Past attempts to identify Chlamydia-specific CTL in vitro have been problematic (18,24,25). However, two laboratories have recently reported cytolysis of Chlamydia-infected cells by CD8 ϩ lymphocytes (3,37).…”
Section: Discussionmentioning
confidence: 99%
“…Because of the obligate intracellular lifestyle of C. trachomatis, it has been thought that CTL may also be involved in immunity to this pathogen. Past attempts to identify Chlamydia-specific CTL in vitro have been problematic (18,24,25). However, two laboratories have recently reported cytolysis of Chlamydia-infected cells by CD8 ϩ lymphocytes (3,37).…”
Section: Discussionmentioning
confidence: 99%
“…Although our findings strongly implicate CMI as a major factor in resolution of MoPn genital infections of mice, the exact effector mechanism remains to be determined. One such mechanism may be that of cell-mediated cytotoxicity of chlamydia-infected cells, although in vitro and in vivo data have yielded variable results (14,16,17). Others have reported that gamma interferon may be important in resolving chlamydial infections, either through macrophage activation (6,25) or by direct inhibition of intracellular replication, as has been demonstrated in various cell culture systems (7,24).…”
Section: Discussionmentioning
confidence: 99%
“…CD8 ϩ T cells comprise roughly 35% of the lymphocytes recovered from MoPn-infected genital tissue (33) and function as professional killer cells as well as a potential source of type 1 cytokines. Although early efforts to detect cell-mediated cytotoxicity against C. trachomatis-infected target cells were unsuccessful (30), cytotoxic T lymphocytes (CTL) were implicated in the detachment of Chlamydia psittaci-infected targets from culture flasks (24) and, later, in the lysis of C. psittaci (8)-or C. trachomatis (5,38,39)-infected cells. However, when the in vivo activity of CTL generated against human C. trachomatis serovars was analyzed, their capacity to protect recipients was attributed to the elaboration of IFN-␥ rather than to direct cell-mediated cytotoxicity (39).…”
mentioning
confidence: 99%